Idiosyncratic neurolinguistic presentations of Chinese speaking primary progressive aphasia individuals: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Tee, Boon Lead; Tempini, Maria Luisa Gorno; Chen, Ta‐Fu; Lo, Raymond Y.; Wong, Adrian
Abstract: Background: Past research on Primary Progressive Aphasia(PPA) has been centered around English language, thus there is limited knowledge to the presentations of linguistic features that differ from the English language. Chinese language possesses numerous linguistic features that contrast significantly from the English language. Chinese language is a tonal and numeral classifier language; hence tones are lexically contrastive and numeral cannot quantify a noun without classifiers. As more than 40% and 20% of living languages worldwide are tonal and numeral classifier languages, investigating these idiosyncratic neurolinguistics features in non‐English speaking PPA individuals may refine the clinical practice paradigm to be more adaptable worldwide. Method: The CLAP (C hinese L anguage A ssessment for P PA) project aims to investigate the neurolinguistics features of Chinese speaking PPA individuals. The CLAP battery consists of fourteen speech and language tasks and this presentation focuses on the tonal and numeral classifier performances as they are idiosyncratic traits of the Chinese language. The tonal perception function is assessed via tonal identification, tonal discrimination, tone‐picture matching, and tone‐word matching tasks. The tonal production performance is evaluated through serial tone reading, repetition of tonal tongue‐twisters, and multi‐tone multi‐repetition tasks. To illustrate classifier function, participants are tasked with producing the accurate classifiers after visual and auditory stimuli of the nouns. Result: The CLAP project recruited 13 healthy controls and 20 PPA individuals (5 nfvPPA, 6 svPPA, and 9 lvPPA) that are native Chinese speakers. Individuals with svPPA were noted to perform significantly lower in the tone‐picture matching task (p=0.024) and classifier task (p<0.0001). Volumes in left inferior temporal and bilateral temporal poles were significantly correlated with the performance in the tone‐picture matching and classifier task respectively. Conversely, individuals with nfvPPA scored substantially lower than healthy controls in all three tone production tasks (p<0.0001, p=0.024, p<0.0001) and lower than other PPA variants in tonal tongue‐twisters tasks. Performance in tonal tongue‐twister tasks was found to correlate with the degree of atrophy in left inferior and superior frontal regions. Conclusion: Tone and classifier tasks can potentially serve as diagnostic and classification tools for PPA individuals that speaks Chinese language and other tonal and numeral classifier languages.